Evaluation of the Effect of Ultrasound on the Synthesis of TiO2 Photocatalysts by Means of its Activity in the Degradation of Dyes - Clara G. Escarcega Ramirez; Marcos May-Lozano; Ricardo López-Medina; María Ortencia González-Díaz; Silvia Cristina Iuga; Juan A. Yañez Varela; Alejandro Alonso-García; Sergio Alejandro Martínez Delgadillo (Chemical Engineering Transactions)
The use of catalysts in the degradation of dyes in aqueous systems has been the focus of intense research due to the toxicity of these pollutants. This study aims to assess the effect on the photocatalytic activity of TiO2-based catalysts subjected to ultrasound at different frequencies and various degrees of hydrolysis during the synthesis process. For TiO2 synthesis using the sol-gel method, ultrasound at frequencies of 250 and 1,000 kHz was used, along with complete hydrolysis (H2O/alkoxide = 8) and incomplete hydrolysis (H2O/alkoxide = 0.5). The catalytic activity of each catalyst was evaluated using a 30 mL sample of Black 5 dye solution, at an initial concentration of 5 ppm. The results indicate that the catalyst synthesized with ultrasound at 1,000 kHz and complete hydrolysis exhibits a shorter degradation time (30 min) compared to the catalyst synthesized without ultrasound under the same H2O/alkoxide ratio (40 min). SEM micrographs clearly show the formation of spheres, especially in catalysts subjected to complete hydrolysis, with and without ultrasound. In UV-Vis DRS spectra, the intrinsic TiO2 absorption band between 200 and 400 nm in the ultraviolet region suggests potential higher catalytic activity in this region. However, the determination of the band gap energy reveals that, although the photocatalyst with incomplete hydrolysis and ultrasound at 250 kHz has a lower band gap energy (2.76 eV), other factors, such as surface area, also influence photocatalytic activity.